Biodegradable polycarbonates from lignocellulose based 4-pentenoic acid and carbon dioxide - Wang, Weiliang; Qu, Rui; Suo, Hongyi; Gu, Yanan; Qin, Yusheng (Frontiers in Chemistry, 2023)
The production of biodegradable polycarbonate by copolymerizing CO2 with epoxides has emerged as an effective method to utilize CO2 in response to growing concerns about CO2 emissions and plastic pollution. Previous studies have mainly focused on the preparation of CO2-based polycarbonates from petrochemical-derived propylene oxide (PO) or cyclohexene oxide (CHO). However, to reduce dependence on fossil fuels, the development of 100% bio-based polymers has gained attention in polymer synthesis. Herein, we reported the synthesis of glycidyl 4-pentenoate (GPA) from lignocellulose based 4-pentenoic acid (4-PA), which was further copolymerized with CO2 using a binary catalyst SalenCoCl/PPNCl to produce bio-based polycarbonates with vinyl side chains and molecular weights up to 17.1 kg/mol. Introducing a third monomer, PO, allows for the synthesis of the GPA/PO/CO2 terpolymer, and the glass transition temperature (Tg) of the terpolymer can be adjusted from 2 oC to 19 oC by controlling the molar feeding ratio of GPA to PO from 7:3 to 3:7. Additionally, post-modification of the vinyl side chains enables the production of functional polycarbonates, providing a novel approach to the preparation of bio-based materials with diverse side chains and functions.